Soliton solutions of Heisenberg spin chain equation with parabolic law nonlinearity - Altun, Selvi; Ozdemir, Neslihan; Ozisik, Muslum; Secer, Aydin; Bayram, Mustafa (SPRINGER, 2023)
In this article, we presented and investigated a model of the (2+1)-dimensional Heisenberg ferromagnetic spin chain (HFSC) equation with parabolic law nonlinearity, for the first time. This study intends on two main elements. The first is to construct the parabolic law nonlinearity form of the HFSC model, and the second is to peruse the effect of this form on the soliton wave behavior. Two different analytical techniques, which are a subversion of the new extended auxiliary equation method and the improved generalized Kudryashov method (iGKM), are applicated to construct the soliton solutions of investigated HFSC form. With the help of these methods, bright, singular, and kink soliton forms have been obtained and their characteristics have been depicted by 2D and 3D diagrams. In accordance with our litterateur investigation, the subject of the study and the results obtained have not been reported before and we can say that the results we have attained will be a guide for researchers who want to study in this field.
Keywords: Ferromagnet Heisenberg; Spin chain; Parabolic law; SAEM246; Improved generalized Kudryashov method; COHERENT; STATES; MODEL; WAVE; Engineering; Physics; Optics